FACTORS AFFECTING CORPORATE VALUES IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE WITH PROFITABILITYAS INTERVENING VARIABLES - simanjuntak, dessyana (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to examine and to analyze the factors that influence the value of campany on manufacture companies listed on the Indonesia Stock Exchange, which were to examine and to analyze factors that influence the value of campany with profitability as intervening variable. The factors used on this research are leverage, assets structure, firm size, likuidity, growth, and audit quality. This research utilizes secondary data. The population of the study was the manufacture industry registered at Indonesia Stock Exchange which was studied from 2012 up to 2014. The method used to determine samples was using purposive sampling method with some fixed criteria with the total number 56 samples of manufacture companies. Analysis tools used in this research consisted of multiple regression analysis and path analysis with the application of SPSS version 20.0. The analysis results of this research to simultaneously show that the variable leverage, assets structure, firm size, likuidity, growth, audit quality influence on the value of company. Partially leverage, likuidity negative insignificant on the value of company, assets structure negative significant on the value of company, firm size, audit quality potive significant on the value of company, growth positive insignificant on the value of company. Profitability variable moderate significant the influence of likuidity on the value of company, and profitability variable moderate insignificant the influence of firm size, growth, audit quality on the value of company, but do not moderate the influence of leverage, assets structure on the value of company.